2021
DOI: 10.36680/j.itcon.2021.008
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality for enabling un- and under-trained individuals to complete specialty construction tasks

Abstract: The construction industry is facing a severe labor shortage that is threatening the performance of projects around the world. Advanced technologies may be able to alleviate the effects of this labor cliff. Specifically, Augmented Reality (AR) has been shown to enhance the performance of current industry professionals completing different construction tasks and is also being explored as a learning tool for students and technicians alike. This research studies if AR can be used as a tool to enable untrained indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…Context awareness in HMDs is essential to facilitate information flow, providing relevant and concise information to users (Bae et al , 2013). Numerous AR/MR-based tools were developed to guide users on assembly tasks, yet most advanced tools can only superimpose assembly instructions without considering the relevance of information (Chalhoub et al , 2021; Chalhoub and Ayer, 2018; Deshpande and Kim, 2018). The complexity of information display may be overwhelming, leading to a decrease in assembly performance.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Context awareness in HMDs is essential to facilitate information flow, providing relevant and concise information to users (Bae et al , 2013). Numerous AR/MR-based tools were developed to guide users on assembly tasks, yet most advanced tools can only superimpose assembly instructions without considering the relevance of information (Chalhoub et al , 2021; Chalhoub and Ayer, 2018; Deshpande and Kim, 2018). The complexity of information display may be overwhelming, leading to a decrease in assembly performance.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…The successful implementation of AR technology in assembly tasks reduced assembly time required by over 80%, positively impacting construction productivity (Chalhoub and Ayer, 2019; Kwiatek et al , 2019). The release of Microsoft HoloLens also enabled the omittance of physical markers (Dallasega et al , 2021), further improving the usability of this AR/MR technology in assembly tasks (Bademosi et al , 2019; Chalhoub et al , 2021; Chalhoub and Ayer, 2018; Deshpande and Kim, 2018; Qin et al , 2021; Wang et al , 2021). Besides that, offsite production time also decreased with the integration of AR/MR technology and robots, decreasing the overall project completion time (Amtsberg et al , 2021; Tavares et al , 2019; Xiang et al , 2021).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Regrettably, there is currently no method for updating the BIM model to reflect such changes made during construction (Gu and London, 2010). Chalhoub et al (2021) demonstrated how AR supports design comprehension among untrained participants to allow them to accurately complete construction tasks that traditionally required professional training. AR is useful to map the as-built and as-planned data in a single digital environment with each component allocated with status such as: ordered, procured, delivered, checked, installed, completed, commissioned, and fixed (Wang et al, 2013).…”
Section: Ar Applications For Productivity Improvementmentioning
confidence: 99%
“…As an additional application, advanced visualization provided by AR in a BIM environment has been used as a tool to enable untrained individuals (ranging from professionals down to unskilled personnel) to complete construction tasks [17]. These tests found out that the use of such a technology can be of great advantage for all the considered categories of workers, with some limitations to the simplest tasks for the under-trained individuals.…”
Section: Scientific Background About Mixed Realitymentioning
confidence: 99%